Patients' risk of causing traffic violations and traffic accidents while driving - Šestan, Nevenka; Dodič Fikfak, Metoda; Balantič, Zvone (Central European Journal of Public Health, 2017)
OBJECTIVES: This study examines whether drivers suffering from epilepsy, chronic alcoholism and/or hazardous drinking, psychoactive substance abuse, other diseases of the nervous system, mental and behavioural disorders, cardiovascular diseases, severe diabetes, and severe eye diseases are at a greater risk of causing traffic accidents and traffic violations than drivers that cause accidents and violations without these diagnoses. METHODS: A case control study was carried out. The cases were drivers checked by a special medical committee in the period observed suffering from the diseases listed above. Matched controls were taken from the cohort of those that caused accidents and violations during the same period observed. The descriptive statistics were followed by calculation of correlations, t-tests and χ2, and the odds ratio. RESULTS: Drivers with referrals for diseases of the nervous system are five times more likely to cause a traffic accident compared to controls (OR=5.18; 95% CI=2.59-10.34); in addition, a high risk is associated with drivers with mental and behavioural disorders (OR=3.64; 95% CI=1.91-6.94), drivers with epilepsy (OR=1.99; 95% CI=1.01-3.92), and drivers addicted to alcohol (OR=1.71; 95% CI=1.01-2.89). CONCLUSION: Drivers suffering from addiction, a disease of the nervous system, or epilepsy are more likely to cause a traffic accident, which is a contribution to the inconclusive findings of previous studies. The multiple reasons for risks of patients suffering from mental and behavioural disorders need to be further investigated.
Keywords: Epilepsy; lidé; Middle Aged; Adult; Case-Control Studies; Risk Factors; rozložení podle pohlaví; Age Distribution; Female; Sex Distribution; Mental Disorders; nemoci nervového systému; Humans; Outpatients; studie případů a kontrol; Substance-Related Disorders; poruchy spojené s užíváním psychoaktivních látek; Automobile Driving; duševní poruchy; lidé středního věku; věkové rozložení; dopravní nehody; mužské pohlaví; epilepsie; ženské pohlaví; Nervous System Diseases; Male; pacienti ambulantní; zločin; Accidents, Traffic; dospělí; Crime; řízení motorových vozidel; rizikové faktory